2013
DOI: 10.1007/s10067-013-2344-x
|View full text |Cite
|
Sign up to set email alerts
|

High-dose methylprednisolone pulse therapy upregulated FcγRIIb expression on B cells in primary Sjögren’s syndrome patients with thrombocytopenia

Abstract: Abnormalities in B cell are characteristic feature of primary Sjögren's syndrome (pSS). As FcγRIIb is a key regulator of B cells, the objective of this study is to investigate the role of the inhibitory receptor FcγRIIb in B cells from pSS patients, and whether glucocorticoid can affect B cell subpopulations or FcγRIIb expression. Thirty pSS patients and 15 healthy controls were enrolled in this study. The results showed that the percentage of memory CD19(+)CD27(+) B cells was significantly lower in pSS patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Chen et al pointed out that the expression of FcγRIIb on B cells was significantly decreased in patients with pSS with severe thrombocytopenia. After high-dose of hormone treatment, the expression of FcγRIIb on memory B cells was up-regulated, and the platelet count was significantly increased (16). Those studies are suggestive of a role of the humoral immune response in platelet destruction which may occur in pSS.…”
Section: Discussionmentioning
confidence: 79%
“…Chen et al pointed out that the expression of FcγRIIb on B cells was significantly decreased in patients with pSS with severe thrombocytopenia. After high-dose of hormone treatment, the expression of FcγRIIb on memory B cells was up-regulated, and the platelet count was significantly increased (16). Those studies are suggestive of a role of the humoral immune response in platelet destruction which may occur in pSS.…”
Section: Discussionmentioning
confidence: 79%
“…The mechanisms of SS with thrombocytopenia is not clear. A few studies have shown that may be a complex immune pathology relating multiple factors,such as P-selectin ( 21), TLR7 signaling pathway (22) and FcγRIIb on B cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…These phenomena are noteworthy. Platelet destruction is often implicated in autoimmune disease, and elevated P-selectin autoantibodies and FcγRIIb suppression on B cells may promote thrombocytopenia in pSS patients [ 23 , 24 ]. Our study suggests that ILD reduces the possibility of thrombocytopenia in SS patients.…”
Section: Discussionmentioning
confidence: 99%